Identification and characterization of long noncoding RNAs involved in the aluminum stress response in Medicago truncatula via genome-wide analysis - Gui, Qihui; Yang, Zhengyu; Chen, Chao; Yang, Feng; Wang, Song; Dong, Rui (Frontiers in Plant Science, 2022)
Numerous studies have shown that plant long noncoding RNAs (lncRNAs) play an important regulatory role in the plant response to environmental stress. However, there are no reports on whether and how lncRNAs regulate and enhance aluminum (Al) stress tolerance in legumes. To determine the role of lncRNAs in the plant Al stress response, we sequenced the contents of 12 strand-specific libraries of the legume model plant species Medicago truncatula. A total of 219.49 Gb clean data were generated: 3,284 lncRNA genes were identified, of which 515 were differentially expressed, and 1,254 new genes were functionally annotated through database alignment. We further predicted and classified putative targets of these lncRNAs and found that they were enriched in biological processes and metabolic pathways such as plant hormone signal transduction, cell wall modification and the tricarboxylic acid (TCA) cycle. Finally, we characterized the functions of 2 Al-activated-malate-transporter-related lncRNAs in yeast and showed that they have biological functions affording Al stress tolerance. These findings suggest that lncRNAs are involved in regulating plant responses to Al stress. Our findings help to understand the role of lncRNAs in the response to Al stress in legumes and provide candidate lncRNAs for further studies.